2016
DOI: 10.1016/j.molp.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

PGR5-PGRL1-Dependent Cyclic Electron Transport Modulates Linear Electron Transport Rate in Arabidopsis thaliana

Abstract: Plants need tight regulation of photosynthetic electron transport for survival and growth under environmental and metabolic conditions. For this purpose, the linear electron transport (LET) pathway is supplemented by a number of alternative electron transfer pathways and valves. In Arabidopsis, cyclic electron transport (CET) around photosystem I (PSI), which recycles electrons from ferrodoxin to plastoquinone, is the most investigated alternative route. However, the interdependence of LET and CET and the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 73 publications
(125 reference statements)
6
91
0
1
Order By: Relevance
“…S13 and S14 C-F). These data support published results demonstrating normal growth of npq1 and npq4 mutants under growth chamber fluctuating light conditions (46)(47)(48). In contrast, the PSII repair-defective mutants were smaller than wild type in the greenhouse, and all but one had significant reductions in PSII activity (Figs.…”
Section: Psii Repair Mutants Are Defective In Growth Acclimation Undersupporting
confidence: 91%
See 1 more Smart Citation
“…S13 and S14 C-F). These data support published results demonstrating normal growth of npq1 and npq4 mutants under growth chamber fluctuating light conditions (46)(47)(48). In contrast, the PSII repair-defective mutants were smaller than wild type in the greenhouse, and all but one had significant reductions in PSII activity (Figs.…”
Section: Psii Repair Mutants Are Defective In Growth Acclimation Undersupporting
confidence: 91%
“…This regulatory complexity is illustrated when considering studies with NPQ-deficient npq1 and npq4 mutants. The observation that npq plants showed normal growth under greenhouse and growth chamber fluctuating light conditions (46)(47)(48) (Fig. 5C and SI Appendix, Figs.…”
Section: Repair Versus Protection Of Psii Under Fluctuating Light Envmentioning
confidence: 96%
“…Furthermore, Fisher and Kramer () reported that Fd and NADPH‐dependent chlorophyll fluorescence rise is achieved by electron donation from Fd to PSII but not PQ‐pool, and the activity was quite small which cannot explain the drastic phenotype of pgr5 mutants. Therefore, it is doubtful whether chlorophyll fluorescence rise assesses the activity of Fd‐dependent CEF‐PSI, and the physiological relevance of PGR5/PGRL1‐dependent CEF is still under debate (Nandha et al , Suorsa et al , , Tikkanen et al , Mosebach et al ). The discordance of PGR5/PGRL1 function would be derived from the lack of direct assessment of Fd during photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…One pathway is mediated through the Fd-dependent PQ reduction, which is sensitive to antimycin A. Two proteins, PROTON GRADIENT REGULATION5 (PGR5; Munekage et al, 2002) and PGR5-like Photosynthetic Phenotype1 (PGRL1; DalCorso et al, 2008) are essential for the pathway to substantially function, although it remains obscure how these proteins are involved in this electron flow (Miyake, 2010;Kramer and Evans, 2011;Strand et al, 2016;Suorsa et al, 2016). The other pathway is mediated by chloroplast NADH dehydrogenase-like (NDH) complex (Yamamoto et al, 2011;Peltier et al, 2016).…”
mentioning
confidence: 99%